PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN LECTORA PADA MATERI HUKUM NEWTION TENTANG GERAK - Muh Arbaun; Tineke Makahinda; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
Learning media is a form of innovation in the learning process. The purpose of this research is to develop interactive learning media using the Lectora application as a media for learning physics in schools and to find out the assessment of material experts, media experts and students of interactive learning media using the Lectora application as a learning medium so that this product is suitable for use in the learning process. This research uses research and development methods or often called Research and Development (R&D). Model adapted from the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate. The ADDIE model is used to be the basis for developing a device or infrastructure for an effective training program. This model uses 5 stages, namely the Analysis stage. , Design, Development, Implementation, and Evaluation After going through the process of the stages carried out, the results obtained are that the interactive physics learning media using the Lectora application has met the criteria as a physics learning media that is suitable for use or used in the learning process at school.